Karl Polanyi E O ‘Grande Debate’ Entre Substantivistas E Formalistas Na Antropologia Econômica (Karl Polanyi and the 'Great Debate' Between the Substantivists and Formalists in Economic Anthropology) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2012)
Na raiz do pensamento Polanyiano, encontra-se a distinção entre economia no sentido substantivo e economia no sentido formal. Com efeito, a concepção substantivista que define a economia como um processo instituído de interação entre o homem e o ambiente natural e social que o rodeia e resulta em contínua oferta de meios para satisfazer as necessidades humanas constitui a base do método preconizado pelo autor: a análise institucional. Com tal distinção, Polanyi (1977a) pretende evitar a "falácia economicista" que consiste na identificação automática da economia com sua forma de mercado. Ao contrário, só na moderna economia capitalista é que um "sistema de mercados formadores de preços" desempenha papel fundamental. Essas questões foram alvo de um "Grande Debate" entre as correntes substantivista – encabeçada por Polanyi – e formalista no contexto da disciplina da Antropologia Econômica.At the root of Polanyian thought, a distintiction can be found between the substantive and formal concepts of the economy. In fact, the substantivist conception, that defines the economy as an instituted process of interaction between man and its natural and social environment, which results in a continuous supply of material means to meet human needs, constitutes the basis of the method recomended by the author: institutional analysis. With this distinction, Polanyi intends to avoid the "economistic fallacy", which consists of the automatic identification of the economy in its market form. Only in the modern capitalist economy does a system of "price-making markets" play a fundamental role. These questions were amply discussed in the so-called "Great Debate" between the substantivist and formalist schools of thought in the discipline of Economic Anthropology. in Economia e Sociedade, Vol. 21, No. 1 (44), pp. 165-195
Sociology; Anthropology
Keywords: economy; formalism; institutional analysis; market; substantivism

Tanzanite: Commodity Fiction or Commodity Nightmare? - Donahue, Katherine Curtis (Social Science Research Network, 2007)
Karl Polanyi's discussion of the commodification of land, labour, and money is useful in analysis not only of nineteenth century markets but also of twenty-first century social and economic developments. This working paper explores the process of commodification of tanzanite, a gemstone discovered in the 1960s south of Mt. Kilimanjaro, Tanzania, and actively mined only since the 1980s. More rare than diamonds because the source area is limited to the Mererani hills east of Arusha, the gemstones reach markets through Maasai middlemen, foreign buyers, processors, cutters, polishers and dealers in Tanzania, India, Hong Kong, and the United States. The U.S. is responsible for 80% of the market for tanzanite. Production of the stone is occasionally slowed by flooding, accidents, and conflict over rights to mining areas. Children and teenagers often work in the tanzanite mines. These miners suffer death and disease not only because of unsafe mine conditions but also because of drug use and HIV/AIDS. Furthermore, this new commodity received close scrutiny after the attacks of September 11, 2001, because of a Wall Street Journal report that members of al Qaeda bought tanzanite for use in funding its networks and activities. This paper explores policy issues raised not only by that report and by global NGOs such as Global Witness, but also by the Tanzanian state, by health and safety workers and the miners and mining companies at Mererani. The paper is based on field interviews with buyers and sellers, in Tanzania and in the United States, as well as analysis of media reports, in order to argue that this particular commodity is, in Polanyi's terms, a fiction, one which has serious policy, social, health, and economic implications.
Anthropology
Keywords: Tanzania; Tanzanite; fictitious commodities; mining

Karl Polanyi - Isaac, Barry L. (Edward Elgar Publishing, 2005)
This unique Handbook contains substantial and invaluable summary discussions of work on economic processes and issues, and on the relationship between economic and non-economic areas of life. Furthermore it describes conceptual orientations that are important among economic anthropologists, and presents summaries of key issues in the anthropological study of economic life in different regions of the world. Its scope and accessibility make it useful both to those who are interested in a particular topic and to those who want to see the breadth and fruitfulness of an anthropological study of economics.
Anthropology
Keywords: economic anthropology; economics and finance; social policy and sociology

The surplus approach, Polanyi and institutions in economic anthropology and archaeology - Cesaratto, Sergio; Bucchianico, Stefano Di (Department of Economics, University of Siena, 2020)
This paper was inspired long ago by Jared Diamond (1997), and in particular by his extensive use of the concept of economic surplus as the key to the development of civilization. Unfortunately, Diamond does not mention the origin of the concept in classical and pre-classical economics, nor does he pay much attention to debates in economic anthropology about the role of economic analysis in studying primitive and ancient economic formations. These debates were the subject of a recent book by Cedrini & Marchionatti (2017), who dispute the neoclassical “imperialist” attempt to occupy the territory of economic anthropology. The authors rely on the institutionalist background provided by Karl Polanyi and his school and by other anthropologists of similar inspiration. Polanyians, however, fail to complete their institutional analysis by anchoring it to the changing modes of generation and distribution of the economic surplus. Yet their emphasis on the need to introduce institutions from the beginning, when speaking of economic surplus, should be taken into consideration by the classical surplus approach
Economics; Anthropology
Keywords: Marx; Polanyi; Sraffa; economic anthropology; economic archaeology; surplus approach